Charakterystyka działalności małych firm innowacyjnych na Dolnym Śląsku - wyniki badań ankietowych - Moszkowicz, Krystyna; Kwieciński, Leszek (Characterization of small innovative businesses' activities in Lower Silesia - The questionnaire results, 2006)
The paper presents the activities of small innovative businesses in Lower Silesia. The assessment of these activities is based on the questionnaire carried out within the European project INNOVIT.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 211-221